PHENOLIC COMPOUNDS AND ANTIOXIDANT ACTIVITY OF GRAPE SEEDS RESIDUES OF PISCO PRODUCTION - Surco Laos, Felipe (2020)
Pisco grapes are 8 known varieties of Vitis vinifera from which pisco is obtained during the pisco production process, by-products such as seeds, skins and others are released from the fruit; the seeds are lately becoming especially important due to their high content of polyphenols and their antioxidant properties. There are several methods for obtaining extracts and in order to obtain extracts with the highest possible polyphenol content in this study, an ultrasonic bath with a solvent system ethanol: water: acetic acid (90/9.5/0.5) is used, which is then taken to dryness in a rotary evaporator. The Total Polyphenols index was determined to be between 402 to 84 μg of seed, flavonoid compound index of 9 to 42 μg of seed; the antioxidant activity by the DPPH method expressed as IC50 between 0.184 to 0.858 mg of extract and by the FRAP method expressed as mM equivalent of trolox from 0.298 to 1.178 mg of extract of the different varieties respectively. The results obtained allow us to project the recovery of these wastes as possible nutraceutical substances.